Implementasi Tingkat Tutur dalam Konsep Uchi-Soto: Studi Kasus Drama Jepang GOKUSEN Season 1 karya Toya Sato - Rosanna Gultom; Rani Arfianty (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Udayana, 2025)
Japanese shows a complex system of speech levels that reflects the speakers politeness towards the conversation partner, in accordance with Japanese cultural values that uphold politiness and respects. This level includes Sonkeigo (recpectful language), Kenjougo (modest language), Teineigo (polite language), and Futsugo (ordinary language). In addition, Japanese communication styles are influenced by the cultural concepts of Uchi (in-group) and Soto (out-group), which determine the dynamics of social interaction. These principles shape language behavior in various domains of society, including in the educational environment. This research examines the application of thi cultural and linguistic framework in the drama Gokusen by Toya Sato. The interaction between Yamaguchi Kumiko (teacher) and class 3D students illustrates the Uchi-Soto dichotomy, where the teacher is seen as an outsider (Soto) and students as an in-group (Uchi). The use of appropriate levels of speech in this relationship highlights traditional Japanese communication strategies. As reflected in this drama, the integration between language and culture emphasizes the importance of harmony and respect in Japanese society. This analysis shows that the concept of Uchi-Soto and levels of speech not only function as linguistic tools, but also reflect broader social norms